Menemukan Kedamaian melalui Ayat-ayat Perang dalam Kitab Tafsir Klasik - Faiz Farichah; Ahmad Musonnif Alfi; Moh. Rozin; Nur Huda (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
Finding Peace through War Verses in the Classical Interpretation BookJihad has become a separate discourse for westerners who consider Islam and its holy book to be a source of legitimacy for acts of terror. Such action was born from a partially understood verse of the Qur'an. Because of that, it needs to be seen that this is not unity, and also remember that the term jihad is not always accompanied by the verse of war. This study aims to comprehensively explore the interpretation of jihad verses in the spectrum of the Koran and Islam. This study uses a qualitative method with an analytical approach to the jihad term. The verses of peace in the Qur'an are presented as a consideration to look comprehensively at the series of meanings of the verses of jihad and war. The results of this study indicate that, First, jihad which has a combative meaning already appears in the earliest verses of jihad, but persuasive understanding of jihad is quite often documented. Second, the war verses show that the legal status and validity period are still being debated. Third, there needs to be an interpretation of verses about peace that are always accompanied by interpretations of jihad verses and war verses